Niko Županič kot slovenski etnolog - Promitzer, Christian (Etnolog. Nova vrsta (Ljubljana), 2003)
The author gives an outline of the history of the Slovene Ethnographic Museum under the supervision of Niko Zupanič, its first director in the years of 1923-1940. After an introduction into the early biography of Zupanič he describes his role in the initial development of the museum which took place in a period which was characterized by poor state funds. Since the role of Zupanič in Slovene ethnology is still disputed, the author tries to show that Zupanič, at least by his professional position, was yet compelled to work as a Slovene ethnologist and therefore has to be given his place in the history of Slovene ethnology.
Keywords: Zupanič, Niko, 1876-1961; biografije; ethnology; etnologija